Flexible Query Answering Systems 2015 Proceedings of the 11th International Conference FQAS 2015, Cracow, Poland, October 26-28, 2015 - Andreasen, Troels; Christiansen, Henning; Kacprzyk, Janusz; Larsen, Henrik; Pasi, Gabriella; Pivert, Olivier; De Tré, Guy; Vila, Maria Amparo; Yazici, Adnan; Zadrożny, Sławomir (Advances in Intelligent Systems and Computing, 2016)
This volume contains the papers presented at the Eleventh Flexible Query Answering Systems 2015 (FQAS-2015) held on October 26-28, 2015 in Cracow, Poland. The international conferences on Flexible Query Answering Systems (FQAS) are a series of premier conferences focusing on the key issue in the information society of providing easy, flexible, and intuitive access to information and knowledge to everybody, even people with a very limited computer literacy. In targeting this issue, the Conference draws on several research areas, such as information retrieval, database management, information filtering, knowledge representation, soft computing, management of multimedia information, and human-computer interaction. The Conference provides a unique opportunity for researchers, developers and practitioners to explore new ideas and approaches in a multidisciplinary forum.  .